Southwest view of the interior Church of St. Helen, Bishopsgate Street - Nash, F.; Howlett, Bartholomew (Tufts Archival Research Center, 2008)
Taken during the repair in 1808. Exhibiting some of the principal Monuments. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.